2002
DOI: 10.1016/s0005-2728(02)00358-4
|View full text |Cite
|
Sign up to set email alerts
|

Bax and heart mitochondria: uncoupling and inhibition of respiration without permeability transition

Abstract: The effects of Bax (full-length, FL, and C-terminal truncated, DeltaC) on respiration rate, membrane potential, MgATPase activity and kinetics of regulation of respiration were studied in isolated rat heart mitochondria and permeabilized cardiomyocytes. The results showed that while both Bax-FL and Bax-DeltaC permeabilized the outer mitochondrial membrane, released cytochrome c and reduced the respiration rate, the latter could be fully restored by exogenous cytochrome c only in the case of Bax-DeltaC, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“… MCU, electrogenic mitochondrial Ca 2+ uniporter; mNCX, mitochondrial Na + /Ca 2+ exchanger; NHE, Na + /H + exchanger; nSR, network SR; PTP, permeability transition pore; “?” – questionable 1 , Akar et al, 2005 2 , Altschafl et al, 2007 3 , Appaix et al, 2002 4 , Arnaudeau et al, 2001 5 , Ban et al, 1999 6 , Bandyopadhyay et al, 2000 7 , Brandes et al, 2002 8 , Budd et al, 1996 9 , Budd and Nicholls, 1996 10 , Cox et al, 1993 11 , Gincel et al, 2001 12 , Jordani et. al., 2000…”
Section: Figurementioning
confidence: 99%
“… MCU, electrogenic mitochondrial Ca 2+ uniporter; mNCX, mitochondrial Na + /Ca 2+ exchanger; NHE, Na + /H + exchanger; nSR, network SR; PTP, permeability transition pore; “?” – questionable 1 , Akar et al, 2005 2 , Altschafl et al, 2007 3 , Appaix et al, 2002 4 , Arnaudeau et al, 2001 5 , Ban et al, 1999 6 , Bandyopadhyay et al, 2000 7 , Brandes et al, 2002 8 , Budd et al, 1996 9 , Budd and Nicholls, 1996 10 , Cox et al, 1993 11 , Gincel et al, 2001 12 , Jordani et. al., 2000…”
Section: Figurementioning
confidence: 99%
“…In the presence of Mg which inhibits MPT, however, Bax led to mild proton leak and cytochrome c release via formation of pores in the OM, independent of MPT [1]. Later it was shown that Bax, Bak and cardiolipin can form a megachannel (<2 MB) in the OM to release cytochrome c and other proapoptotic molecules sequestered in the intermembrane space [45].…”
Section: Role Of Mpt In Ischemia/reperfusion (Ir) Injurymentioning
confidence: 99%
“…Release by 2-APB-Release of the mitochondrial intermembrane protein cytochrome c typically accompanies the osmotic swelling and rupture of the outer membrane evoked by activation of the PTP (45)(46)(47). Loss of mitochondrial matrix pyridine nucleotides is another measure of the PTP, distinguishing it from a mechanism of depolarization mediated by activation of a "low conductance" pore (48).…”
Section: Inhibition Of Ca 2ϩ -Induced Mitochondrial Cytochrome C and mentioning
confidence: 99%